IMCC USM TO FURTHER INTERNATIONALISE THE UNIVERSITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 20 April 2016 – The rebranding exercise of the Universiti Sains Malaysia (USM) International Office (IO) to become the International Mobility and Career Centre (IMCC) has provided a new dimension in the planning of programmes for USM students to facilitate more exchange of ideas with the international students in addition to having a better appreciation of the diversity from the many different countries.